PENGARUH PENDIDIKAN POLITIK TERHADAP PARTISIPASI POLITIK MAHASISWA PRODI PPKn FKIP UNIVERSITAS MUHAMMADIYAH PONOROGO PADA PELAKSANAN PEMILIHAN UMUM KEPALA DAERAH PROVINSI JAWA TIMUR TAHUN 2018 - Arifin Arifin; Sunarto Sunarto; Hadi Cahyono (EDUPEDIA, 2018)
The purpose of this study is (1) to know whether there is influence of political education on the political participation of  Civic Education Students of Teacher Training and Education Faculty  Muhammadiyah University of Ponorogo on the implementation of  East Java Regional Head General Election in 2018. (2) To find out how much influence is given between political education on the political participation of Civic Education  Students, Teachers Training and Education Faculty Muhammadiyah University of  Ponorogo in the implementation of general elections East Java Regional Head of 2018. This research uses quantitative methods conducted at the Muahammadiyah University of  Ponorogo with the respondents are students of Civic Education Teacher Training and Education Faculty University Muhammadiyah of  Ponorogo 2018 who have the right to vote in East Java Regional Head General Election 2018. Data collection techniques using questionnaires and documentation techniques. The population in this study were 69 respondents, while the sample used  many 55 respondents.The research results obtained from this research is the positive and significant influence given political education against political participation with sig 0.000 0,05 and political education gives effect of 0,535 or 53,5%.